FERTILISASI IN VITRO DALAM TINJAUAN MAQĀṢID ASY-SYARĪ‘AH - Anwar, Syamsul (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Having been commonly practiced, in vitro fertilization (fertilization in a tube/baby tube program) is one of the controversial medical practices both for religious reasons and for ethical and moral reasons. From the ethical/moral point of view, the problem lies in the fact that the implication of such a practice may result in the destruction of the remaining unused embryos. In this article, the writer argues from the point of view of maqāṣid asy-syarī‘ah that the practice of in vitro fertilization is much needed by the infertile couples who want to have children. The embryo's moral status starts from the implantation of the blastocyst in the women’s uterine wall, so that the zygote of fertilization in the pre-implantation tubes does not have a moral status yet.[Walaupun telah jamak dilakukan, fertilisasi in vitro (pembuahan dalam tabung/bayi tabung) merupakan salah satu praktis medis yang konroversial baik karena alasan agama maupun karena alasan etika dan moral. Dari segi etika/moral, permasalahannya adalah implikasi dari praktik itu yang berakibat pada pemusnahan sisa embrio yang tidak digunakan. Dalam tulisan ini penulis berargumerntasi dari sudut pandang maqāṣid asy-syarī‘ah bahwa praktik fertilisasi dalam tabung sangat dibutuhkan oleh pasangan tidak subur yang mendambakan keturunan. Status moral embrio dimulai sejak implantasi sehingga zigot hasil fertilisasi dalam tabung praimplantasi belum memiliki status moral].